Högskolans ansvar Principer för utveckling av den högre - Casson, Andrew (Ubiquity Press, 2015)
What should a university be? How can universities make a sounder and more lasting contribution to better lives and better societies in a globalised world? From a Swedish perspective, this new book challenges current ideas about what higher education is for. It presents fifteen principles for future development that range from a discussion of the nature of knowledge to the responsibility of the university in the development of society. Universities must become better at allowing and encouraging students to develop independence of thought and action through self-formation, bildung, and personal growth rather than merely preparing them for a specific job, the books says, using a historical perspective to consider these issues.